2019
DOI: 10.7320/flmedit29.075
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity, chorology and conservation of the lichen flora in Tessala Mountains forest (North-West Algeria)

Abstract: online. This study is a first investigation of the lichen flora of the Tessala Mountains green oak forest in northwestern Algeria. Field research using stratified sampling method allowed us to propose a first checklist of the lichen flora of this region containing 53 taxa with taxonomic, chorological and biogeographical data in NorthWest Africa (Algeria, Morocco and Tunisia) of each of them. Among these lichens, 3 taxa are cited for the first time for the NW Africa. Comments on some interesting species are add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…However, Otálora et al (2017) have concluded that the biogeographic analysis of Pectenia plumbea indicates that the Mediterranean basin is the most likely ancestral distribution area of this species. Pectenia plumbea occurs in Western Europe, according to COSEPAC (2010), but in Algeria, it has been reported in previous studies (Flagey, 1896;Harmand, 1909or Werner, 1949 as well as more recently Boutabia, 2016;Hamralaine et al, 2019), but never in the current study area (Edough Peninsula).…”
Section: Resultssupporting
confidence: 46%
“…However, Otálora et al (2017) have concluded that the biogeographic analysis of Pectenia plumbea indicates that the Mediterranean basin is the most likely ancestral distribution area of this species. Pectenia plumbea occurs in Western Europe, according to COSEPAC (2010), but in Algeria, it has been reported in previous studies (Flagey, 1896;Harmand, 1909or Werner, 1949 as well as more recently Boutabia, 2016;Hamralaine et al, 2019), but never in the current study area (Edough Peninsula).…”
Section: Resultssupporting
confidence: 46%